Puasa di Era Digital: Relevansi Tasawuf dalam Menghadapi Tantangan Spiritual Kontemporer - Muhammad, Abdy Nur; Anggraini, Reski (NALAR, 2025)
The article aims to analyze the relevance of the concept of fasting from a Sufi perspective for formulating a practical approach to overcoming spiritual challenges in the digital age, including digital overload, fast-tainment, and “digital sin.” Employing a qualitative library research with a theological-philosophical analytical framework, the study draws on the Quran, Hadith, and Al-Ghazali's Ihya 'Ulum al-Din as primary sources. Data was analyzed through a hermeneutic interpretation of religious texts to build an argument about the relevance of Sufi fasting in the digital context. The study found that the common understanding of fasting (shaumul umum) is no more relevant in the digital age. In this context, the concept of shaumul khawwas, which involves controlling sinful actions, as well as Sufi practices such as mujahadah an-nafs and digital detox (as contemporary ‘uzlah), becomes an essential “spiritual firewall.” The findings show that fasting in the digital age requires a holistic approach that extends beyond the physical aspect, making the Shaumul Khawwas framework an urgent necessity. The findings in this article contribute to providing practical guidance for Muslims to maintain spiritual integrity during fasting amid the onslaught of digital technology, filling a gap in previous studies related to fasting.